PERAN GEMBALA JEMAAT SEBAGAI PEMIMPIN DALAM MENINGKATKAN PERSAHABATAN DENGAN SEMUA ORANG - Marthen Mau (STT Saint Paul Bandung, 2022)
A good and true friendship is a friendship that is built continuously both long distance and face to face. Therefore, in the context of pastoral ministry, a church pastor needs to be friendly with all members of his congregation. The pastor's role is to encourage all members of the church to increase friendship among fellow congregations and make friends with all people. Friendship with all people is highly valued by Christ Jesus through His word. This study aims to explain the role of the church pastor as a leader in increasing friendship with all people. To answer the problems and research objectives, qualitative research methods are used by applying a library approach. The results of the research to be achieved are the pastor of the church as a spiritual leader who plays an intense role in being able to encourage believers or the congregation to increase friendship with all people according to the teachings of Jesus Christ in His word.